2023
DOI: 10.3389/fnut.2022.1108098
|View full text |Cite
|
Sign up to set email alerts
|

Role of circulating sphingolipids in lipid metabolism: Why dietary lipids matter

Abstract: Sphingolipids are structural components of cell membranes and lipoproteins but also act as signaling molecules in many pathophysiological processes. Although sphingolipids comprise a small part of the plasma lipidome, some plasma sphingolipids are recognized as implicated in the development of metabolic diseases and cardiovascular diseases. Plasma sphingolipids are mostly carried out into lipoproteins and may modulate their functional properties. Lipids ingested from the diet contribute to the plasma lipid poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Therefore, further longitudinal studies with multiple ethnic groups and larger sample sizes are needed to verify our findings. Sixth, it is important to consider the influence of dietary factors on lipid profiles [ 57 , 58 , 59 ], especially since substantial differences in dietary patterns have been observed between Dutch South Asians and Dutch white Caucasians [ 60 ]. However, our study did not gather specific information regarding the participants’ dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further longitudinal studies with multiple ethnic groups and larger sample sizes are needed to verify our findings. Sixth, it is important to consider the influence of dietary factors on lipid profiles [ 57 , 58 , 59 ], especially since substantial differences in dietary patterns have been observed between Dutch South Asians and Dutch white Caucasians [ 60 ]. However, our study did not gather specific information regarding the participants’ dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, total dietary fat intake was significantly higher during pregnancy than postpartum. Although study samples were collected after a meal, there is no evidence that plasma sphingolipids are altered postprandially [ 27 ]. Quantitative analysis was limited by the availability of sphingolipid analytical standards.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary intervention studies in human beings have demonstrated the impact of lipid consumption on circulating sphingolipids and cardiovascular risk markers. 48 Consumption of saturated fatty acids increases plasma ceramide concentrations along with alterations in triglyceride-rich lipoproteins, whereas consumption of polar lipids decreases circulating levels of ceramides and other sphingomyelins. 48 Thus, the findings from the CASPID study could inform dietary intervention strategies aimed at minimization of risk and optimization of cardiometabolic health.…”
Section: Discussionmentioning
confidence: 99%